Characterization of Constructed Wetlands for Wastewater Treatment in Costa Rica - Aguilar Álvarez, Ronald Esteban (2025)
In response to the need for decentralized wastewater treatment solutions in rural and peri-urban areas, constructed wetlands emerge as an ecological, low-cost, and adaptable option for tropical conditions. This study analyzes the location, design, and technical characteristics of horizontal subsurface flow constructed wetlands in Costa Rica. Through field visits conducted between March 2022 and June 2023, 81 systems built since 2004 were characterized. The implementation of constructed wetlands has shown informal technical standardization, driven by local guidelines and material availability, which has generated consistent patterns in their dimensions, depth, substrate type, and vegetation. The findings indicate that 96% of these systems treat greywater and are predominantly located in Puntarenas (53%) and Guanacaste (19%). Most systems feature surface areas of 1-15 m² and an average depth of 0,75 m, with plastic sheeting as the primary waterproofing material (90%). The most common substrate used is cobbles at the inlet and outlet, and crushed rock in the middle section. A total of 44 plant species were identified, with Canna indica and Heliconia sp. being prominent; their distribution showed a dependence on climate, based on chi-squared analysis. An interactive cartographic viewer accompanies the study to facilitate spatial analysis and data updates. The results reveal a limited and empirical development of this technology, lacking consolidated databases or systematic technical monitoring. The study proposes its integration as a decentralized sanitation strategy in communities not connected to formal systems, through public policies that recognize its effectiveness and replicability.